THE GREEN MSME DRYING TECHNOLOGY MODEL AND ITS IMPACT ON THE ADDED VALUE OF COFFEE FARMERS IN ACEH - Dedy Darmansyah; Hartini; Qhisthina Atikah; Ina Yuyun (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Drying is a critical post-harvest stage for coffee, as it directly determines the final quality, economic value, and ultimately, farmers' income. Most farmers in Aceh Tengah and Bener Meriah still rely on conventional methods, such as drying coffee directly on tarps or non-standard racks. These practices often result in high moisture content, significant physical defects, and consequently, lower selling prices. This study analyzes the effectiveness of a "Green MSME" drying rack constructed from wood and food-grade mesh in improving coffee quality and farmer income, while also evaluating its alignment with sustainability and circular economy principles. Using a descriptive-comparative quantitative approach, the research involved 30 farmers applying four different drying methods. The results demonstrated that the Green MSME technology yielded the best coffee quality, with an average moisture content of 11.2% and a defect rate of 6.1%, which is superior to tarpaulin drying (12.8% and 11.3%, respectively). The added value for Green MSME coffee reached IDR 77,500 per kg (9.9% higher than the traditional method), leading to an income increase of 1.19% to 13% per 500 kg of dry beans. Furthermore, the Green MSME model supports sustainability through greater energy efficiency, waste reduction, the use of eco-friendly materials, and enhanced potential for quality certification. In conclusion, this innovation has proven to be feasible, economical, and consistent with green production principles, making it a viable model for widespread replication to develop the smallholder coffee agribusiness in Aceh.